2017
DOI: 10.5468/ogs.2017.60.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Genital tract cavernous hemangioma as a rare cause of postpartum hemorrhage

Abstract: Cavernous hemangiomas rarely involve the female genital tract. It is difficult to identify vascular malformations when these lesions are concealed in the vagina or deep vulva area. We present a rare case of vaginal cavernous hemangioma in a 30-year-old primiparous woman with an early severe postpartum hemorrhage (PPH) and delayed continuous bleeding from the episiotomy site. She was treated successfully with transarterial embolization of the left vaginal artery. To our knowledge, this is the first reported cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Seven vaginal hemangiomas have been reported to date (Table 1) [1,[4][5][6][7]. Six cases (75%) were associated with pregnancy, in particular, late pregnancy, in addition to the present case.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Seven vaginal hemangiomas have been reported to date (Table 1) [1,[4][5][6][7]. Six cases (75%) were associated with pregnancy, in particular, late pregnancy, in addition to the present case.…”
Section: Resultsmentioning
confidence: 57%
“…However, an episiotomy was performed at the previous delivery, at the same place as the vaginal hemangioma. Yu et al recently also mentioned that the vaginal hemangioma in terminal pregnancy was observed at the previous episiotomy [7]. Therefore, the previous episiotomy may have affected the formation of the vaginal hemangioma in late pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…However, there are also publications reporting necrosis of the uterus, sciatic nerve, and bladder if not performed under the appropriate conditions (13,14) . Although uterine atony is the most common cause of PPH, vascular pathologies such as arteriovenous malformation (AVM), hemangioma, and vascular tumors must be borne in mind for patients with massive hemorrhage (15) . Variations in the pelvic vascular anatomy in particular may cause serious bleeding in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…There are reported cases in the literature in which selective pelvic embolization was performed due to PPH of different etiologies. Yu et al (15) reported the efficacy of selective arterial embolization in a patient with vaginal hemangioma who remained undetected in antenatal follow-up and who experienced massive bleeding after vaginal delivery with episiotomy. The development of collateral vessels between the inferior mesenteric artery (IMA) and uterus is not normally observed.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas can occur systemically, but the most common sites are the skin of the head and the neck [ 1 ]. Hemangiomas rarely occur in female genital organs, such as the uterus, vagina, and perineum [ 2 ].…”
Section: Introductionmentioning
confidence: 99%